What can neuroscience learn from contemplative practices? - Bernard J. Baars (Frontiers Research Topics, 2016)
A recent wave of brain research has advanced our understanding of the neural mechanisms of conscious states, contents and functions. A host of questions remain to be explored, as shown by lively debates between models of higher vs. lower-order aspects of consciousness, as well as global vs. local models. (Baars 2007; Block, 2009; Dennett and Cohen, 2011; Lau and Rosenthal, 2011). Over some twenty-five centuries the contemplative traditions have also developed explicit descriptions and taxonomies of the mind, to interpret experiences that are often reported in contemplative practices (Radhakrishnan & Moore, 1967; Rinbochay & Naper, 1981). These traditional descriptions sometimes converge on current scientific debates, such as the question of conceptual vs. non-conceptual consciousness; reflexivity or "self-knowing" associated with consciousness; the sense of self and consciousness; and aspects of consciousness that are said to continue during sleep. These real or claimed aspects of consciousness have not been fully integrated into scientific models so far. This Research Topic in Consciousness Research aims to provide a forum for theoretical proposals, new empirical findings, integrative literature reviews, and methodological improvements inspired by meditation-based models. We include a broad array of topics, including but not limited to: replicable findings from a variety of systematic mental practices; changes in brain functioning and organization that can be attributed to such practices; their effects on adaptation and neural plasticity; measurable effects on perception, cognition, affect and self-referential processes. We include contributions that address the question of causal attribution. Many published studies are correlational in nature, because of the inherent difficulty of conducting longitudinal experiments based on a major lifestyle decision, such as the decision to commit to a mental practice over a period of years. We also feature clinical and case studies, integrative syntheses and significant opinion articles.